A new Brazilian species of Isotomiella (Collembola: Isotomidae), with notes on I. bidentata Delamare Deboutteville, 1950 and I. amazonica Oliveira & Deharveng, 1990 - de Mendonça, Maria Cleide; Abrantes, Eduardo Assis (Zootaxa, 2007)
In the present article we describe a new species Isotomiella barrana sp. nov. from “Parque Nacional da Tijuca”, “Restinga de Maricá” and “Restinga da Marambaia”; redescribe I. bidentata Delamare Deboutteville, 1950 found for the first time in Brazil and enlarge the occurrence of I. amazonica Oliveira & Deharveng, 1990 to the Rio de Janeiro State.